Corresponding divine and human agency in Paul: an exegetical study of practical agency - Heo, Sangmin (2021)
This thesis aims to analyse how divine and human agency in Paul work and correspond in the soteriological, religious, and logical actions through the exegetical approach. While postSanders scholarship tends to focus on the agency issues regarding soteriology by comparing the Pauline writings to the Judaism and Hellenistic literatures in the Second Temple period, the collaborative and extensive exegetical study with the fresh approach on the divine and human agency has been missing. For that reason, this thesis astutely selects and fully examines seven actions from the entire undisputed letters of Paul which display the capricious, paradoxical, and fluctuating characters. Those selections are not just confined to the soteriological actions but also the practically religious and logical actions. To untangle the entwined agencies in those capricious, paradoxical, and fluctuating actions, this thesis answers the twofold questions: ‘who does what’ and ‘in what senses of doing it’ by analysing the usages of each action (the verb including its cognates) and the exegetical studies with special regard to agency. Paul argues that divine agency enables and provides the foundation for human agency by the preceding divine action, and human agency practically and freely performs the action in the sphere of divine agency. Both agencies are united in synergistic power and authority over sin and its vile actions, but not in autonomy and cognition. So they ‘co-work’ corresponding to each other to practically work out in the lives of believers. Finally, the relation between divine and human agency can be called corresponding ‘co-workers’ as Paul described himself (1 Cor 3.9, 2 Cor 6.1).